2023
DOI: 10.1186/s12931-023-02403-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of cellular senescence in idiopathic pulmonary fibrosis

Abstract: Background Cellular senescence is a cell fate in response to diverse forms of age-related damage and stress that has been implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF). The associations between circulating levels of candidate senescence biomarkers and disease outcomes have not been specifically studied in IPF. In this study we assessed the circulating levels of candidate senescence biomarkers in individuals affected by IPF and controls and evaluated their ability to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Results from this study are complementary to previous analy- and with clinical measures of biological age and functional limitations (Aversa et al, 2023;Fielding et al, 2022;Schafer et al, 2020;Tanaka et al, 2018Tanaka et al, , 2020 were quantifiable in their plasma and were, at least in part, longitudinally reduced by the CR intervention.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Results from this study are complementary to previous analy- and with clinical measures of biological age and functional limitations (Aversa et al, 2023;Fielding et al, 2022;Schafer et al, 2020;Tanaka et al, 2018Tanaka et al, , 2020 were quantifiable in their plasma and were, at least in part, longitudinally reduced by the CR intervention.…”
Section: Discussionsupporting
confidence: 58%
“…Unfortunately, none of the SASP components studied to date is unique to senescent cells and, certainly, the secretome of other cell types may be affected by CR. We note, however, that the circulating biomarkers assessed in this study were based on an expanded panel of biologically diverse senescence‐related proteins we previously developed by reviewing the literature, screening their abundance in in vitro models of senescence, and demonstrating detectability in human blood in contexts associated with increased senescent cell burden (Aversa et al., 2023 ; Fielding et al., 2022 ; Schafer et al., 2020 ). In addition, our in silico analysis of an RNA sequencing data set derived from the adipose tissue specimens of a small subset of CALERIE™ participants randomized to CR (Spadaro et al., 2022 ) demonstrated a significant reduction in the SenMayo gene set at both 12 and 24 months compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, we exploited the literature and the secretome of several human cell types induced to senescence in vitro to develop a candidate panel of senescence biomarkers, comprised of cytokines, chemokines, matrix remodeling proteins, growth factors, and other proteins, that could be reliably measured in the blood of humans (Schafer et al., 2020 ). We have observed expected changes in their circulating abundance in conditions associated with increased senescent cell burden, including advanced chronological age, frailty, disability, and chronic disease (Aversa, Atkinson, et al., 2023 ; Fielding et al., 2023 ; Schafer et al., 2020 ). Most recently, we studied biospecimens and clinical data from the Comprehensive Assessment of Long‐term Effects of Reducing Intake of Energy (CALERIE™) study and demonstrated that participants randomized to 2 years of calorie restriction had reduced concentrations of senescence biomarkers at Year 1 and Year 2 compared to those randomized to an ad libitum diet (Aversa, White, et al., 2023 ).…”
mentioning
confidence: 99%